Traces of Metre and Prosody in Instrumental Music - Grimalt, Joan (Res Facta Nova, 2025)
This paper explores the possibilities of prosody in instrumental music as an analytical tool. Examining some lyrical themes for orchestra or piano from Corelli to Mahler, the information which metre and prosody reveal about a virtual singing and a virtual text is researched. Topic theory and musical rhetoric are taken as indispensable complements to this intertextual research, to confirm or nuance the findings. The author has been recollecting examples for years now. Surprisingly, not even new musicology, sensitive to such intersections, had gone into this field yet.